Three new South American species of Salacia with fasciculate inflorescences (Celastraceae, Hippocrateoideae) - Lombardi, Julio Antonio (Missouri Botanical Garden, 2007)
Three new fasciculate flowered species of Salacia L. (Celastraceae, Hippocrateoideae) from the Amazon basin are described: S. acevedoi Lombardi is distinguished by its small flowers, stamens with short filaments, disc connate to ovary, and size of fruits; S. negrensis Lombardi differs by its habit, characteristics and shape of leaves, flower diameter, features and size of stamens, and number of ovules: and S. odorata Lombardi is characterized by its long pedicels, conical flower buds, strongly adherent petals. and flat disc with fimbriate outer border.
Keywords: Brazil; Celastraceae; Ecuador; Hippocrateoideae; IUCN Red List; Peru; Salacia